Peran Wanita Dalam Menumbuhkan Wira Usaha Guna Mendukung Ekonomi Keluarga Perumahan Melalui Pengolahan Makanan Jagung Sebagai Alternatif Pengganti Makanan Pokok - Dosen Tetap AKS Semarang, Kurnianingsih (Teknis, 2017)
The production of corn are currently faced on processing the utilization of crop will be an alternative food, therefore, the role of women is dearer to fill the void of women in residential district of Banyumanik who was as a housewife, at this momment, finding additional needs through entrepreneurship to support the economic of family in increasing their life. In food priority in developing National Security, so there are three reasons for the review: 1) access of nutrition is good enough for human rights, 2) food nutrition consumption is the basis for the establishment of the qualified human resources, 3) food priority is the basic for economic security, even the national food security. Utilization of corn as alternative food had a good role, to some products, ingredients of corn already can be developed in the type of food menu depends on the processed that the ingredients is corn flour.Keyword : Role of Women, Food Processing.